Community Control in the Housing Commons: A Conceptual Typology. Issue 1 (17th September 2021) - Durose, Catherine; Richardson, Liz; Rozenburg, Max; Ryan, Matt; Escobar, Oliver
We advance theorizing on the governance of the commons through a configurative comparative analysis (CCA) of community control in the housing commons. We focus our analysis on community land trusts (CLTs), which are increasingly recognised as a potential governance mechanism for collective access to housing provision for low-income communities. Through systematic comparative analysis of CLTs in the US and UK, we extend the existing evidence base and develop a conceptual typology of community control in the housing commons. The typology suggests that whilst some social purposes for CLTs may align with notions of the commons – enrichment of community politics, conservation of community life, or creation of participatory governance – other CLTs focus on housing provision as a means of making a broader contribution to the social economy, or as an asset-lock to enable wider provision for affordable housing. By understanding this differentiation, we challenge the assumption that design principles or governance mechanisms are sufficient for or inherently offer a singly clear route to community control, and recognise that community control is achieved through different pathways informed by the multiple configurations of dynamics between different aspects of governance, as usefully illuminated by CCA. Our approach demonstrates the value to scholarship and activism on the commons of systematic comparative analysis in order to interrogate the expansion of the commons not only in practice but in spirit.